The Adaptation of Building Information Modelling (BIM) on Existing Building As-Built Plan For Future Engineering Reference - Mustaffa, Nor Syazwani; Zakaria, Muhammad (Recent Trends in Civil Engineering and Built Environment, 2021)
Building Information Modelling (BIM) is a modern alternatives technique that combines traditional approach with construction schemes. BIM is also a collaboration method, fpcused on different software solutions used by the architecture, engineering and construction (AEC) industry. The scattered data and information makes the project complicated, confusing and hard to interpret. The main research objectives are to analyze and design of an existing building of Kuarters Pangsapuri Jelatek by using Tekla Structural Designer software in accordance to Eurocode Standard and this study contain four (4) phases which are obtain and study the existing buiding, transfer the details of the structure from As-Built to Tekla Structural Designer to get the result, perform a sketching of the building using Autodesk Revit and compare the analysis result by referring the Eurocode and British Standard. Tekla Structural Designer software and Autodesk Revit is used in this research to achieve the objective of this research. This study have a restriction from provided information from the As-Built drawing plan. The existing As-Built plan does not provided the detailed data about the building such as the size of the structural elements, column elements and other related . Therefore, the software will facilitate in the detailed documenting of steel and concrete design in 3 dimensional concept. As a result, the model elements provide a direct presentation of data from the building database for future technical reference.